The Relationship Between Cognitive Functions and Sport-Specific Motor Skills in Elite Youth Soccer Players - Scharfen, Hans-Erik; Memmert, Daniel (Frontiers in Psychology, 2019)
The aim of the present study was to examine the relationship between basic cognitive functions and sport-specific motor skills in elite youth soccer players. A total of 15 elite youth soccer players aged 11-13 years performed a computer-based test battery measuring the attention window (AW), perceptual load (PL), working memory capacity (WMC), and multiple object tracking (MOT). Another set of tests was used to asses speed abilities and football-specific technical skills (sprint, change of direction, dribbling, ball control, shooting, juggling). Spearman’s correlation tests showed that the diagonal AW was positively associated with dribbling skills (rs = .656) which indicates that a broader AW could be beneficial for highly demanding motor skills like dribbling. WMC was positively related to dribbling (rs = .562), ball control (rs = .669) and ball juggling (rs = .727). Additionally, the cumulated score of all cognitive tests was positively related to the cumulated motor test score (rs = .614) which supports the interplay of physical and psychological skills. Our findings highlight the need for more and especially longitudinal studies to enhance the knowledge of cognition-motor skill relationships for talent identification, talent development, and performance in soccer.